Odpowiedzi

Najlepsza Odpowiedź!
2009-11-29T15:20:20+01:00
2(x-3)-4(2x-5)=1+3x
2x-6-8x+20=1+3x
-6x+14=1+3x
-9x=-13 |:(-9)
x=13/9
x=1⁴/₉
2009-11-29T15:22:49+01:00
2(x-3)-4(2x-5)=1+3x,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, 2x-6-8x+20=1+3x,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, 2x-8x-3x=1+6-20,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, -9x=-13→x=¹³/₉,,,,x=1⁴/₉
2009-11-29T15:26:01+01:00
2(x-3)-4(2x-5)=1+3x
2x-6-8x+20=1+3x
-6x+14=1+3x /-1
-6x+13=3x /-3x
-9x+13=0 /-13
-9x=-13 /*-1
9x=13 / :9
x=1,(4)